Reconstructing Gender Roles in Contemporary Muslim Families: Islamic Family Law Analysis in the Role of Wives as Online Motorcycle Taxi Drivers - Idris, Ahmad Rusyaid; Wahyuni, Riski; Harahap, Fikrah Elhifzi; Khusaini, Muhammad; Sufiandi, Idris (Legitima : Jurnal Hukum Keluarga Islam, 2025)
Purpose – This study aims to analyze the role of wives as online motorcycle taxi drivers in helping to meet household needs using the framework of contemporary Islamic family law. Methods – Field studies were conducted in this study with a socio-legal approach. Data was collected through interviews with five wives who work as online motorcycle taxi drivers in Metro City, and analyzed using the Mubādalah theory based on the principles of justice and equality. Findings – The findings of this study indicate that the obligation to earn a living is a form of protection for the family, and the role of wives as online motorcycle taxi drivers is part of modern society's efforts to achieve mutuality and cooperation in family life. Wives as online motorcycle taxi drivers are a form of loyalty in helping to create a harmonious family life and reduce the economic burden on the family. However, the main responsibility for earning a living remains the husband's obligation, and the wife helps her husband as part of a mutually beneficial relationship that brings goodness. Research limitations - The small sample size is a limitation of this study; however, it provides a comprehensive conceptual framework for addressing the challenges of contemporary families. Contribution – This study provides new insights into the relationship between the roles of husbands and wives in overcoming family challenges.